2014
DOI: 10.1017/s0142716414000010
|View full text |Cite
|
Sign up to set email alerts
|

Isolating stereotypical gender in a grammatical gender language: Evidence from eye movements

Abstract: The present study investigates the effects of stereotypical gender during anaphor resolution in German. The study aims at isolating the effects of gender-stereotypical cues from the effects of grammatical gender. Experiment 1 employs descriptions of typically male, female, and neutral occupations that contain no grammatical cue to the referent gender, followed by a masculine or feminine role noun, in a reaction time priming paradigm. Experiment 2 uses eye-tracking methodology to examine how the gender typicali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
5
16
1
Order By: Relevance
“…However, these had been carefully pre-tested drawing from the same population, and they were carefully selected based on their mean and standard deviation (see the Materials and method section for details). Further backing up our claim that the asymmetry we found is meaningful is the fact that this asymmetry has been found in two other eye-tracking studies [58,59] and two priming experiments investigating response times [60] and event-related potentials [61]. …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, these had been carefully pre-tested drawing from the same population, and they were carefully selected based on their mean and standard deviation (see the Materials and method section for details). Further backing up our claim that the asymmetry we found is meaningful is the fact that this asymmetry has been found in two other eye-tracking studies [58,59] and two priming experiments investigating response times [60] and event-related potentials [61]. …”
Section: Discussionsupporting
confidence: 79%
“…They found an N400-like effect when a masculine pronoun was presented after a stereotypically female prime, but not when a feminine pronoun was presented after a stereotypically male prime. Reali et al [59], in an attempt to disentangle the effect of a role noun’s grammatical gender and its stereotypicality in German, used descriptions of role nouns in their eye-tracking stimuli instead of the role nouns themselves (e.g., makes appointments , deals with the correspondence in an office as a description of secretary ). They found that following female role noun descriptions, participants had difficulty when the described person (e.g., the secretary) was revealed to be a man.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that children were less likely to think of males engaging in traditional feminine activities ( Henry-nurse ) than the other way around ( Mary-doctor ). As noted above, a similar asymmetry has recently been found in young adults ( Siyanova-Chanturia et al, 2012 , see also Cacciari and Padovani, 2007 ; Irmen et al, 2010 ; Reali et al, 2014 ).…”
Section: Introductionsupporting
confidence: 82%